2014
DOI: 10.1111/cei.12264
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors and CD40 modulate each other's expression affecting Leishmania major infection

Abstract: SummaryToll-like receptors (TLRs) recognize pathogen-associated molecular patterns and results in innate immune system activation that results in elicitation of the adaptive immune response. One crucial modulator of the adaptive immune response is CD40. However, whether these molecules influence each other's expression and functions is not known. Therefore, we examined the effects of TLRs on CD40 expression on macrophages, the host cell for the protozoan parasite Leishmania major. While polyinosinic-polycytidy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Neutrophil granule enzymes, such as NE, could activate the microbicidal functions of macrophages through interactions with surface receptors (49). TLR2 and TLR4 could be trigged by proteolytically active NE on infected macrophages, leading to an oxidative response, TNF-a production, and parasite killing (26,(50)(51)(52). Our data indicate that each en-FIGURE 7.…”
Section: Discussionmentioning
confidence: 89%
“…Neutrophil granule enzymes, such as NE, could activate the microbicidal functions of macrophages through interactions with surface receptors (49). TLR2 and TLR4 could be trigged by proteolytically active NE on infected macrophages, leading to an oxidative response, TNF-a production, and parasite killing (26,(50)(51)(52). Our data indicate that each en-FIGURE 7.…”
Section: Discussionmentioning
confidence: 89%
“…In our preceding report, we showed that astrakurkurone could inhibit the intracellular amastigotes, the pathogenic stage in mammalian host, by inducing ROS in macrophages, with a 50% inhibitory concentration of 2.5 g/ml in vitro (16). Interestingly, astrakurkurone also induced the generation of NO, an essential antiamastigote effector molecule (21,26,(28)(29)(30)(31)(32), considerably in uninfected macrophages and significantly in infected macrophages. The induction of inflammatory response was further reflected by an induction of a proinflammatory cytokine, IL-12, and a fall of the anti-inflammatory cytokines IL-10 and TGF-␤ by astrakurkurone.…”
Section: Discussionmentioning
confidence: 90%
“…It preserves the benefit of this molecule as antileishmanial therapy, because endogenous TNF-␣ has been reported to induce apoptosis in host macrophages (43). A significant surge in the nitric oxide level in infected macrophages can be justified due to the engagement of CD40 (21) and TLR9 (30) or ultimately because of the activation of NF-B by astrakurkurone. It has been well documented that all TLRs can enhance CD40 expression, while CD40 augments the expression of only TLR9 (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations